Pengaruh Pandemik Covid-19 dan Volume Penjualan Terhadap Total Pendapatan Pada PT Internusa Medika Surabaya - Setyowati, Lis; Elfiana , Cicilia Tika (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
This research aims to describe the effect of pandemic covid-19 and sales volume on PT Internusa Medika income both partially and simultaneously. This type of research is quantitative research with associative-casual approach. The used of research population is accountancy report of PT Internusa Medika in January 2019 till May 2019 with the research sample in 29 months. Data collected by observation method, documentation method, internet research, and library research. The data analysis method used multiple linier regression analysis, F test, T test, and R Square. The results showed that there was a positive and significant effect partially and simultaneously by Pandemic covid-19 on the PT Internusa Medika income. There was a positive and significant effect partially and simultaneously sales volume on the PT Internusa Medika income.